Hubungan Status Sosial Ekonomi Keluarga dengan Status Gizi Remaja Usia 11 – 15 Tahun di Pusat Pengembangan Anak (PPA) ID-127 Kota Manado - Rombot, Dina V.; Palandeng, Henry Malcom Frank; Tumimomor, Anggreiny M. (UNIVERSITAS SAM RATULANGI, 2013)
The successful development of a nation is determined by the availability of qualified human resources and it depends on good nutritional status. The good nutritional status of adolescent was specify by family socioeconomic status, if the condition of the socioeconomic status are good, the better nutritional status. A familyâ€™s socioeconomic status is based on parental education, parental occupation and family income. This research has been doing to know the association between family socioeconomic status with nutritional status of adolescents ageâ€™s 11 â€“ 15 years old at Child Development Centre (CDC) ID-127 Manado City. The design research is an analytic research with cross sectional approach. There are 90 samples taken from 92 people of total population who are willing to be sampled. Data obtained from direct measurement and interview questionnaire. The anthropometric measurements calculated using z-score and spearman rho for statistical test to prove the hypothesis of this research.The result showed there was no association between family socioeconomic status and nutritional status of adolescents ageâ€™s 11 â€“ 15 years old with the value of Ï = 0,083; Ï = 1,00; Ï = 0,455 (Ï > 0,005) are indicated there was no association between parental education, parental occupation and family income with nutritional status of adolescents ageâ€™s 11 â€“ 15 years old at Child Development Centre (CDC) ID-127 Manado city. Keywords: socioeconomic status, nutritional status